The Sly Guy - Ausbeth-Ajagu, Anuli (Evans Brothers (Nigeria Publishers) Ltd, 2012)
This is an intriguing story of a young, handsome guy called Sly,who every girl would want to be friends with.
Keywords: Juvenile Fiction